Coupling study on ecological resilience and urban-rural integrated development in China - Wang, Yue; Song, Mengfei; Zhu, Siyan; Jiang, Zhihui; Zhang, Zhen (Frontiers in Environmental Science, 2025)
Scientific understanding of China’s ecological resilience and urban-rural dynamics supports comprehensive environmental and socio-economic advancement. This research utilizes an integrated coupling coordination framework to examine the relationship among ecological resilience and rural-urban dynamics in 31 Chinese provinces from 2011 to 2022. The spatiotemporal dynamics of ecological resilience-urban-rural coupling are examined through kernel density estimation and complementary methods. An LSTM network is used to forecast trends (2023-2030) and identify underlying patterns. Panel VAR is applied to explore the dynamic interactions between ecological resilience and urban-rural dynamics. The findings reveal regional disparities, with urban-rural dynamics consistently outperforming ecological resilience across all regions, while exhibiting lower variability. The coordination between ecological resilience and urban-rural dynamics shows an upward trend with moderate concentration and distinct regional variations. Projections for 2023-2030 indicate fluctuating yet upward trends in provincial-level coordination. Provincial development transitions from near-imbalance and marginal coordination pre-2026 to primary and intermediate coordination phases post-2026. The coordination levels across the four regions are ranked in descending order as follows: the eastern part of China, followed by the western, midland, and northeast areas. Nationwide analysis reveals significant autocorrelation in ecological resilience (5% level) and urban-rural dynamics (1% level), with urban-rural dynamics exerting a stronger influence on ecological resilience (1% level). This study elucidates the ecological resilience-urban-rural nexus, offering empirical foundations for China’s sustainable urban-rural development strategies.